RETRACTED: Mendelian randomization based on immune cells in diabetic nephropathy - Zhou, Ye; Zhang, Hengyan; Yan, Heguo; Huang, Changxing; Liu, Yangwen (Frontiers in Endocrinology, 2024)
Background: DKD, a leading cause of chronic kidney and end-stage renal disease, lacks robust immunological research. Recent GWAS utilizing SNPs and CNVs has shed light on immune mechanisms of kidney diseases. However, DKD's immunological basis remains elusive. Our goal is to unravel cause-effect relationships between immune cells and DKD using Mendelian randomisation.We analyzed FinnGen data (1032 DKD cases, 451,248 controls) with 731 immunocyte GWAS summaries (MP=32, MFI=389, AC=118, RC=192). We employed forward and reverse Mendelian randomization to explore causal links between immune cell traits and DKD. Sensitivity analysis ensured robustness, heterogeneity checks, and FDR correction minimized false positives.Results: Our study explored the causal link between diabetic nephropathy (DKD) and immunophenotypes using two-sample Mendelian Randomization (MR) with IVW.Nine immunophenotypes were significantly associated with DKD at p<0.05 after FDR correction. Elevated CD24, CD3 in Treg subsets, CD39+ CD4+, and CD33-HLA DR-AC correlated positively with DKD risk, while CD27 in B cells and SSC-A in CD4+ inversely correlated. Notably, while none showed significant protection, further research on immune cells' role in DKD may provide valuable insights.The results of this study show that the immune cells are closely related to DKD, which may be helpful in the future clinical study.